Public Health Classifications – based on the Public Health Classifications Project Final Report (Phase One) - Kapka, Lucyna; Cyranka, Małgorzata (Polish Journal of Public Health, 2009)
Existing public health classifi cations do not capture important areas of public health, which include its functions, the methods and interventions used to achieve these, the health issues and determinants of health that public health activities address, the resources and infrastructure they use, and the settings in which they occur. It became apparent that a simple, one-dimensional classifi cation system for public health could not satisfy the needs.The Public Health Classifi cations Project report presents version one of a classifi cation of public health. This paper describes the development of an initial version of such a classifi cation.There was a consensus among the public health experts consulted, that a public health classifi cation should be multi-dimensional, and there was broad agreement on the top-level classes that should be included. The public health classifi cation captures the important dimensions of public health activity. It will facilitate the organisation of information so that it can be used to address questions relating to any of these dimensions, either singly or in combination.